Conjugal DNA Transfer in Sodalis glossinidius, a Maternally Inherited Symbiont of Tsetse Flies - Christopher G. Kendra (American Society for Microbiology, 2020)
ABSTRACT Stable associations between insects and bacterial species are widespread in nature. This is the case for many economically important insects, such as tsetse flies. Tsetse flies are the vectors of Trypanosoma brucei, the etiological agent of African trypanosomiasis—a zoonotic disease that incurs a high socioeconomic cost in regions of endemicity. Populations of tsetse flies are often infected with the bacterium Sodalis glossinidius. Following infection, S. glossinidius establishes a chronic, stable association characterized by vertical (maternal) and horizontal (paternal) modes of transmission. Due to the stable nature of this association, S. glossinidius has been long sought as a means for the implementation of anti-Trypanosoma paratransgenesis in tsetse flies. However, the lack of tools for the genetic modification of S. glossinidius has hindered progress in this area. Here, we establish that S. glossinidius is amenable to DNA uptake by conjugation. We show that conjugation can be used as a DNA delivery method to conduct forward and reverse genetic experiments in this bacterium. This study serves as an important step in the development of genetic tools for S. glossinidius. The methods highlighted here should guide the implementation of genetics for the study of the tsetse-Sodalis association and the evaluation of S. glossinidius-based tsetse fly paratransgenesis strategies. IMPORTANCE Tsetse flies are the insect vectors of T. brucei, the causative agent of African sleeping sickness—a zoonotic disease that inflicts a substantial economic cost on a broad region of sub-Saharan Africa. Notably, tsetse flies can be infected with the bacterium S. glossinidius to establish an asymptomatic chronic infection. This infection can be inherited by future generations of tsetse flies, allowing S. glossinidius to spread and persist within populations. To this effect, S. glossinidius has been considered a potential expression platform to create flies which reduce T. brucei stasis and lower overall parasite transmission to humans and animals. However, the efficient genetic manipulation of S. glossinidius has remained a technical challenge due to its complex growth requirements and uncharacterized physiology. Here, we exploit a natural mechanism of DNA transfer among bacteria and develop an efficient technique to genetically manipulate S. glossinidius for future studies in reducing trypanosome transmission.